2004
DOI: 10.1080/00207390310001623481
|View full text |Cite
|
Sign up to set email alerts
|

Learning statistical concepts

Abstract: In order to learn the concept of statistical techniques one needs to run real experiments that generate reliable data. In practice, the data from some well-defined process or system is very costly and time consuming. It is difficult to run real experiments during the teaching period in the university. To overcome these difficulties, statisticians developed simple and very economical experiments, which can be performed in the class by the students. Stone studied the variation, bias, stability and statistical qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, the characteristics of greater Zab river was studied by other researchers during 2004 -2005 [33][34] , they explained the high turbidity of the river's water by inefficient treatment or resuspension of sediment and the surface run off that enters the river. Their results showed that Greater Zab River water can not be used for drinking directly.…”
Section: Riversmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the characteristics of greater Zab river was studied by other researchers during 2004 -2005 [33][34] , they explained the high turbidity of the river's water by inefficient treatment or resuspension of sediment and the surface run off that enters the river. Their results showed that Greater Zab River water can not be used for drinking directly.…”
Section: Riversmentioning
confidence: 99%
“…At the same time, these authors observed a low level of nitrate which was attributed to the effect of macro-microphyte which utilizes the inorganic nitrate. Akram et al 34 , monitored monthly the quality of water samples from Kasnazan Impoundment during Aug 2004 -Feb 2005. Statistical analysis indicated that there was a significant difference between kahreez (site 1) and other sites in TDS and HCO 3 values while there was no significant difference in K concentration between the locations or times.…”
Section: Kasnazan Impoundment In Erbilmentioning
confidence: 99%